Optimasi Pengembangan Express Feeder pada Jaringan Distribusi untuk Mengurangi Drop Voltage Menggunakan Particle Swarm Optimization - Syaepul Alam, Dendi; Busaeri, Nundang; Risnandar, Muhammad Aris (Fakultas Teknik Universitas Garut, 2025)
Drop voltage is one of the main problems in the distribution system which has an impact on reducing the quality of voltage received by customers. This research aims to reduce voltage drop in the distribution system according to the standard voltage drop tolerance limit of 5% set in SPLN 72: 1987 on the CLDG extension by applying the Particle Swarm Optimization (PSO) optimization method in the development of express feeders. The CLDG feeder has a radial network topology with a channel length of 32.75 km with loads spread along the network. The simulation process was carried out to analyze the existing conditions and after optimization, using Backward Forward Sweep (BFS) power flow with the help of MATLAB R2023b software for its application and validated using ETAP 19.0.1. The results showed that PSO successfully determined the optimal location of express feeder development from bus B01 to bus B18, with the placement of a new LBS at bus B17. This development reduced the number of critical buses from 52 to 16 buses, and the maximum voltage drop from 9.86% to 6.67%.